Is Price Flexibility Destabilizing - Driskill, Robert; Sheffrin, Steven M. (American Economic Review, 1986)
Sluggish wages and prices are generally the culprits in models of unemployment and business fluctuations. Price flexibility in standard fix-price models would restore the economy to full employment. This line of reasoning has often been at the heart of proposals to reform institutions in order to restore flexibility to wages and prices. There is, however, a strand of macroeconomic thought that questions the wisdom of too much price flexibility. John Maynard Keynes raised the issue in chapter 19 of the General Theory by noting that a deflation could raise real interest rates and thereby impede a return to full employment. In his 1975 paper Keynesian Models of Recession and James Tobin develops this point in a formal model. Low prices work to move the economy to full employment but falling prices, to the extent that they lead to expectations of deflation, raise the real interest rate (through the Mundell effect) and move the economy away from full employment. Instability is likely to occur if expectations of inflation adjust rapidly to actual inflation and the real interest rate effect is large. Our historical experience does include significant episodes where either reductions in inflation or actual deflation were accompanied by high real interest rates. Although other factors could be responsible, the experiences of the Great Depression, the Latin American countries in the late 1970's and the United States in the early 1980's all add surface plausibility to the real interest rate deflation link and thus to one aspect of the Keynes-Tobin story. Recently, Bradford De Long and Lawrence Summers (1984) have argued that the decrease in the variance of output following World War II can be largely attributable to the decrease in wage and price flexibility in the postwar era. The reason output fluctuations are smaller today is precisely because the Keynes-Tobin destabilizing mechanism is less operative today.' This paper examines whether increased price flexibility can be destabilizing in a version of John Taylor's contract model (1979, 1980) extended to include real interest rate effects. Taylor's model includes both backward and forward elements in wage-setting behavior and thus permits some rationality in the wage-setting process. We find that even with this limited degree of rationality, increased wage flexibility leads to a decrease in both the variance of output and the variance of prices. Nicholas Carlozzi and Taylor (1983) introduce the real rate of interest into a staggered contract framework and discuss in general terms and through simulations the effects that changing real rates may have on the system. They do not, however, study the effects of potential instability through increases in wage flexibility or provide any analytical results. They provide an extensive discussion of the implications of alternative policy rules on the stochastic behavior of the economy. We first add the real interest rate to the standard Taylor model and derive the solution and prove key analytical results. These results are further buttressed by simulations.